Utilización de aplicativo Remind como herramienta de apoyo en la enseñanza de investigación básica - Matzumura-Kasano, Juan P. (2021)
Objective. The main goal of this study was to determinate the relationship between the use of Remind app as a support tool and the academic performance in teaching a research course to medical students in 2020. Methods. Correlational and cross-sectional research with medical students from a private university from the basic research course. This was applied to a non-probabilistic sample made of 96 participants. A 3 dimensioned and 24 questions questionnaire was used in the Likert scale, and contains (0.94) reability. Descriptive statistics and bivariate analysis were used. Results. The average age was 23.2 ± 5.9 years old, 68.8% were female. 96.9% used the app for the first time and 72.9% considered Remind as a safe app. Academic dimension: 85% agreed with the app as it allows to send reminders of the upcoming classes. Learning dimension: 79% learned to manage their time in a better way and 77% considered it a valuable form of learning. Personal dimension: 71% agreed in using it and 69% recommends using it in other courses. 85.4% are the favorable percentile. The students that used the app, had better grades. Conclusion. The app is favorably accepted; it facilitates the learning process and is positive to students’ grades.